"POST-MINING REALITY" in Western Europe: Selected Collieries in Belgium and France Following Discontinuation of Coal Mining. Issue 11 (February 2019) - Langer, Piotr
Abstract: There are numerous areas in Europe that were developing and functioning based on traditional industries, such as coal mining. These include among others: The Ruhr and Saar Coal Basins in Germany, Upper Silesia in Poland, Limburg in Holland or Nord-Pas-de-Calais in France. The spaces of industrial regions and cities, including those related to coal mining, have undergone a fundamental metamorphosis following the economic transformation which – in western Europe – started in the second half of the last century. A vast majority of collieries have been shut down and joined the group of former industrial facilities of great adaptation potential, commonly referred to as brownfields. The article contains a concise analysis of the condition of former mining facilities in two countries in Western Europe – Belgium and France, as well as a synthetic evaluation of the significance of these facilities for contemporary urban spaces. The discussion has been based on the Author's field research carried out in August 2017, focused on now defunct collieries that have been adapted to serve new public utility functions. The primary objective of the research was to diagnose the following problems related to the development of former mining facilities and grounds, with special focus on the complexes of shaft headframes and their accompanying dumps: a. the contemporary practical significance of adapted collieries; b. spatial and compositional role of former mining facilities; c. how the surviving collieries affect preservation of the identity of cities and regions historically related to coal mining. The above problems have been discussed on the basis of and illustrated with the examples of former Belgian collieries: "C-Mine" in Genk and "Bois du Cazier" in Marcinelle, as well as two collieries in France, in the Nord-Pas-de-Calais region: "Delloye" in Lewarde and "Dourges" in Oignies. The conclusions stemming from the conducted research and the article itself may prove useful in evaluation of the results of actions undertaken in relation to the shutdown collieries. They may also provide a good starting point for similar research in other mining regions in Europe, particularly in the areas where the process of the mining industry transformation is still in progress or has only just begun.